Management of Corneal Decompensation 4 Decades After Sputnik Intraocular Lens Implantation. Issue 1 (January 2015) - Hirji, Nashila; Nanavaty, Mayank A.
Abstract : Objectives: We report an unusual case of corneal decompensation occurring four decades after complicated cataract extraction with implantation of a Sputnik intraocular lens (IOL) and highlight the clinical and practical issues faced in managing corneal decompensation with a Sputnik IOL. Methods: A 72-year-old woman presented with deterioration of the vision in her left eye, four decades after intracapsular cataract extraction with Sputnik IOL implantation. Ocular examination revealed diffuse corneal edema and thickened vitreous strands in the anterior chamber. Her best-corrected visual acuity (BCVA) worsened to 6/60 within 3 months. Anterior vitrectomy and inferior iridectomy combined with Desçemet-stripping automated endothelial keratoplasty was performed. Results: The procedure was successful, with the patient achieving best-corrected visual acuity of 6/6 at 8 months postoperatively. Conclusion: Corneal decompensation after Sputnik IOL implantation can occur four decades later. When the historical preoperative visual acuity is good in such cases, careful anterior vitrectomy with Desçemet-stripping automated endothelial keratoplasty provides good visual rehabilitation. Abstract : Supplemental Digital Content is Available in the Text.